I2 -λ-statistically convergence of double sequences in fuzzy normed spaces - Kişi, Ömer; Kişi, Ömer (Journal of Intelligent Fuzzy Systems, 2019)
In this paper, we have investigated I2-?-statistically convergence for double sequences in fuzzy normed linear spaces, where ? = (?r) and ? = (?s) be two non-decreasing sequences of positive real numbers, each tending to ? and such that ?r+1 ? ?r + 1, ?1 = 1; ?s+1 ? ?s + 1, ?1 = 1. Some inclusion relations between I2-statistically convergent and I2-?-statistically convergent double sequences in fuzzy normed linear spaces are established.
Keywords: Statistical convergence; I-convergence; ?-convergence; Fuzzy norm; Double sequences